Pemberdayaan Perempuan Melalui Workshop Ecoprint Ibu PKK Desa Dalangan dalam Meningkatkan Kreativitas - Megananda Arga Buana; Agus Isdiyanto; Saptariana; Agung Pramana (Universitas Negeri Semarang, 2025)
The purpose of this community service activity is to empower women in Dalangan Village through an ecoprint workshop with the target community of PKK mothers. This workshop is designed to improve the creativity and skills of village women in utilizing natural materials for ecoprint products. The community service method applied is training. The community service activity was carried out on Saturday, August 3, 2024 at 16.00 WIB in Dukuh Dalangan, Dalangan, Tulung District, Klaten Regency. The results of the ecoprint training were an increase in the technical skills of mothers in making products. Initially, PKK mothers did not know about ecoprint and had never made ecoprint cloth products. PKK mothers were very enthusiastic in participating in the training from start to finish. With this training, an effective strategy was found to increase the creativity and welfare of women at the village level by making sales.